CONDITIONS OF THE FORMATION OF PROFESSIONAL COMPETENCE OF FUTURE OFFICERS OF ROCKET AND ARTILLERY ORDNANCE - Oleh M. Maslii (Вісник Університету імені Альфреда Нобеля. Серія Педагогіка і психология)
This article is devoted to the study of the issue of pedagogical conditions of the formation of professional competence of future officers of rocket and artillery ordnance. Scientific research done by educators-researchers on organization of military training at higher military educational institutions has been analyzed. It has been pointed out that effective influence on the formation of professional competence of future officers of rocket and artillery ordnance is exerted by the following pedagogical conditions: increase of motivation in the process of formation of readiness for professional activities; integration of general and special knowledge in the professional competence of future officers of rocket and artillery ordnance; formation of skills of combat response of future officers of rocket and artillery ordnance; increase of professional competence of scientific and pedagogical workers of military-vocational training disciplines. The pedagogical condition for raising the level of motivation for professional activity involves the readiness of future officers to be engaged in operational and combat activities and depends on the motivational sphere of military specialists and the degree of formation of their orientations at professional activities. The Implementation of the pedagogical condition of integration of general and special knowledge of professional competence of future officers is manifested by the formation of professional competence of military specialists on the basis of the integration approach. The pedagogical condition for the formation of combat response skills of future officers of rocket and artillery ordnance is based on the problem of combat response of future officers in the course of their professional activities, in particular during the operation of the united forces in the eastern regions of Ukraine. The implementation of pedagogical condition for increasing the professional competence of scientific and pedagogical workers depends on the level of their competence. Professionalism of scientific and pedagogical workers of higher military educational institutions is manifested in the ability to see and form educational and service tasks on the basis of analysis of difficult conditions of a combat situation on a different terrain day and night, unplanned use of different techniques and methods of action, and find the best ways to solve them. The current issue of the system of higher military education is to increase the level of readiness of scientific and pedagogical workers for innovation, research activities and creative development of high-tech weapons and equipment, the exploitation of which is impossible without the use of information and communication technologies. The general condition that promotes the development of all components in training of future officers of rocket and artillery ordnance is the implementation of a pedagogical system for the formation of professional competence of cadets at higher military education institutions. It involves the preparation of officers of rocket and artillery ordnance, various trainings on their readiness to use information and communication technologies in their professional activities, introduction of special courses to ensure control over the development of this process and its subsequent correction, etc.